Pengaruh Aktivitas Fisik Selama Kehamilan dan Luaran Kehamilan: Literatur Review - Okkeu Azizah Calbara; Dwi Izati Budiono (Universitas Batanghari Jambi, 2023)
Pregnancy is a natural physiological process. The average length of human gestation is 280 days, or 40 weeks, from the first day of the woman's last menstrual period. Physiological changes occur during pregnancy. Changes that occur in pregnant women are caused by biological, social and psychological pressures. Physical changes that occur in pregnant women can cause discomfort in the third trimester, such as constipation and insomnia. The purpose of this literature review is to determine the effect of physical activity on the course and outcome of pregnancy. The literature used is literature published within the last 5 years (2018 to 2022), is primary research and research is located in Indonesia. The keywords used in this literature search were physical activity, pregnant women and pregnancy. Search for articles using search engines in the Garuda Portal. The results of this literature review are moderate-intensity physical activity that is carried out regularly and directed can reduce the discomfort of pregnant women in the third trimester and minimize unnecessary interventions during labor.